SOCIAL RANK STYLES, MACHIAVELLIANISM AND THE ATTITUDE TOWARD CONSPICUOUS CONSUMPTION - Mitić, Anja; Petrović, Ivana; Đurić, Veljko (Primenjena psihologija, 2018)
Conspicuous consumption describes signalling of one’s buying power in order to impress others and secure and/or preserve a favourable place in a social hierarchy. The current study, involving 200 junior and senior high school students from Serbia, examined inclination for lavish spending on brand name clothes in relation to social dominance. Our aim was to examine a predictive relationship between an exploitative interpersonal strategy (marked by Machiavellianism, Leadership, and Ruthless Self−Advancement), and the attitude toward conspicuous consumption. Our respondents with high esteem of power, emanating from the principal position within a group, and prone to Machiavellianism and Ruthless Self−Advancement, had a positive attitude toward conspicuous consumption (an indirect measure of the actual behaviour). Although one’s attitude toward conspicuous consumption is likely to be multifaceted, our findings suggest that a positive attitude towards conspicuous consumption may be an accompanying ingredient of the opportunistic and calculating life strategy. The results indicate that conspicuous consumption is most likely embedded in the social ranking processes.